The technology of developing critical thinking through reading and writing (CTRW): a path to shaping a mature personality - Shvarts , Alevtina (The Lingua Spectrum, 2025)
The article explores the technology of developing critical thinking through reading and writing (CTRW) as one of the most effective approaches to shaping a mature, responsible, and thoughtful personality. The CTRW method consists of three key stages – evocation, realization of meaning, and reflection – each aimed at activating students’ cognitive processes, developing the ability to analyze, compare, draw conclusions, and express their opinions with reasoned arguments. Reading and writing are viewed not as ends in themselves, but as tools that facilitate deeper understanding, independence, and intrinsic motivation for learning. The author emphasizes the importance of creating a developmental educational environment where students become active participants in the learning process. CTRW technology not only enhances knowledge acquisition but also fosters 21st-century skills such as critical thinking, communication, creativity, and collaboration. The article concludes by highlighting the significance of implementing this methodology in educational practice as a key condition for developing a mature personality.